Pengaruh ElNino pada Gelombang Signifikan di Perairan Indonesia: Achmad Fahruddin Rais - Achmad Fahruddin Rais Achmad Fahruddin Rais (Jurnal Fisika dan Aplikasinya, 2019)
In the previous studies, the influence of ElNino on significant waves was not able to be analyzed properly because the simulation model used did not cover the super ElNino period. Therefore, a new research needs to be done based on data in the period of super ElNino. Before analyzing, I assess the accuracy of wavewatch III (WW3) model significant wave by calculating correlation and root mean square error (RMSE) on significant wave of the altimeter satellite. The influence of ElNino on significant waves is obtained from the correlation between the oceanic nino index (ONI) 3.4 and the significant waves of WW3. I also calculate the ratio between significant wave composites of ElNino / LaNina and ElNino super events towards normal significant waves. The results show that theWW3 significant wave has good accuracy in Indonesian waters. ElNino and LaNina have a strong influence on significant waves in the Java Sea and Sunda Strait at period of December-January-February (DJF). ElNino (LaNina) is able to reduce (increase) the significant wave height until 30%to the normal condition in Java Sea and Sunda strait. In extreme cases, super ElNino is able to reduce a significant wave height until 50% to the normal condition.